Pengaruh Program Sanitasi Total Berbasis Masyarakat (STBM) Pilar Pertama sebagai Pilar Utama untuk Mewujudkan Perilaku Higienis dan Saniter di Kelurahan Morokrembangan - Cezia Putri Erika; Aussie Amalia (Lembaga Pengembangan Kinerja Dosen, 2024)
Community-Based Total Sanitation (STBM) is a strategy to sanitation development that was established in response to the high prevalence of diarrhea caused by poor sanitation in Morokrembangan Village, which resulted from the community's behavior of defecating anywhere. This approach facilitates the community empowerment process to analyze the situation and risks of environmental pollution caused by open defecation. This research aims to determine the effect of the first pillar of the Community Based Total Sanitation (STBM) program, namely Stop Open Defecation (STOPS) in Morokrembangan Village. Using the method proposed by finsterbusch and motz, namely the Single Program Before-After assessment/evaluation. The existence of the STBM program has had a positive influence on society. The positive influence here can be seen from various aspects, such as positive influence in the form of changes in the environment, health, socio-culture, physical condition of latrines.